Survey On The Nutritional Status Of PPLP Athletes In The Taekwondo Sports Branch, Riau Province - Nadya Karlina; Rices Jatra (Outline Journal of Education, 2023)
This study aims to determine the nutritional status of PPLP taekwondo athletes in Riau Province. This research is quantitative descriptive. Using the total sampling method with a total sample of 7 PPLP taekwondo athletes. Data collection included nutritional status and body fat percentage by taking anthropometric data on body weight, height and measuring upper arm circumference. Based on the results of data processing, it showed that most of the athletes had normal nutritional status (86%). And most athletes have good nutritional body fat percent (57%). Thus it can be said that the PPLP taekwonso athletes' nutritional status survey has normal nutritional status and good nutritional body fat percent.